Management of Krukut Puskesmas District Tamansari in Increasing The Achievement of Covid-19 Vaccination - Fung Li; Paisal Halim (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2023)
The spread of COVID-19 is still high, so it is hoped that a solution from the government to suppress its spread is expected. The strategy is from the top level, namely the government to the lowest level, especially the puskesmas. Which is at the forefront of providing vaccinations to the community. The data analysis method used is descriptive qualitative method through interviews with several informants and using the triangulation method. The title of this research is the strategy of puskesmas leadership in increasing vaccination achievement by using Wheelen and Hunger's theory. The results of the strategy of the puskesmas leadership in increasing vaccination achievements based on the principles of planning, organizing, directing and controlling have maximized coordination between institutions and local community leaders. And the inhibiting factors for leadership in increasing vaccination achievements include coordination that does not run smoothly, the limited number of healthy health workers during the high spread of COVID-19, the emergence of hoaxes about vaccines, low public awareness to implement health protocols, and solutions for leaders. Puskesmas to improve vaccination achievement is to improve coordination between lines. Maximizing health workers and asking for additional health workers for vaccination, providing understanding for the community about these hoaxes and inviting people to comply with health protocols.